Strategi Pengelolaan Dana Zakat Digital Dalam Upaya Pemberantasan Kemiskinan - M Aidil Muttaqin; Muhammad Aga Syauqi; Aulia Dwi Septiarini; Nyanyu Debi Agnes Monica; Siti Haniyah; Anugrah Nurfajri (Journal of Economics and Business, 2024)
ABSTRACT Zakat is an amaliyah worship that has a high social dimension and function towards the gift of Allah SWT. Apart from that, zakat also has the value of social solidarity, a statement of humanity and justice, and proof of Islamic brotherhood. Zakat is the 3rd pillar of Islam, which was obligatory when the Prophet was in Medina, precisely in the 2nd year of the Hijriah. At that time, zakat was one solution to overcome and avoid the economic downturn at that time. This journal discusses strategies that can be used to optimize the digital zakat system to eradicate poverty. This journal uses qualitative research methods and is descriptive.  With the conclusion that the distribution of zakat funds is right on target both in the form of direct cash assistance and economic empowerment programs.   ABSTRAK Zakat merupakan ibadah amaliyah yang mempunyai dimensi dan fungsi sosial yang tinggi terhadap karunia allah SWT. Selain itu, zakat juga memiliki nilai solidaritas sosial, pernyataan rasa kemanusiaan dan keadilan, serta pembuktian akan persaudaraan islam. Zakat merupakan rukun islam yang ke 3, yang diwajibkan pada masa Rasulullah berada di Madinah tepatnya pada tahun ke 2 Hijriah. Pada masa itu zakat merupakan salah satu solusi dalam mengatasi dan menghindari dari keterpurukan ekonomi pada masa itu. Jurnal ini membahas tentang Strategi- strategi yang dapat digunakan dalam mengoptimalkan sistem zakat digital untuk memberantas kemiskinan. Adapun jurnal ini menggunakan metode penelitian kualitatif dan bersifat deskriptif. Dengan kesimpulan Penyaluran dana zakat tepat sasaran baik dalam bentuk bantuan langsung tunai dan program pemberdayaan ekonomi.